Analysis of collaboration between AstraZeneca and the higher education sector in the UK. Issue 6 (December 2022) - Rezaei, Asma; Kamali, Ali Reza
Collaboration between industry and universities is a driving force for scientific and technological advancements. Due to the role of AstraZeneca (AZ), a British–Swedish multinational pharmaceutical and biotechnology company, in combatting the COVID-19 pandemic, an analysis of the collaboration between the company and universities in the UK is of importance. Here, the collaboration of AZ with top UK universities, namely the University of Cambridge (UoC), the University of Oxford (UoO), Imperial College London (ICL) and University College London (UCL), is investigated. The investigation is based on two different measures: the well-developed Salton's measure and the scientific impact of collaboration (SIC). The former considers the scientific articles published by each party as well as the joint articles published in the period 2010–2021. The SIC, which is introduced for the first time in this article, involves the number of joint articles and citations to them in the same period. An unprecedented increase in the value of the Salton's measure for the collaboration between AZ and UoO is observed in 2021, and this is discussed with regard to the development of the Oxford–AstraZeneca COVID-19 vaccine. The findings support the argument that strategic alliances are more important than co-location in drug discovery and development.